LESSON ORGANIZATION MODEL BASED ON PERSONAL EDUCATION IN SECONDARY SCHOOLS - Yorqin Shukurov (Bright Mind Publishing, 2025)
In recent years, the interest of foreign and domestic scientists in the field of secondary education, their interest in the individualization of various concepts and methods, and their interest in personalization have increased significantly. In the theory and practice of person-oriented education, the importance of taking into account the interaction of cognitive, emotional, and behavioral mechanisms of personal activity is increasing. Within a person-centered approach, it is important to use some methods of influencing the cognitive, emotional, and behavioral aspects of learners based on the tasks of each phase of teaching. For example, at one stage of the lesson, the dynamic approach is useful and expands the scope of knowledge of the learner, at another stage - it helps to develop new, constructive actions of behavior.